Crystal structure of 4,4′-bis(dibromomethyl)-1,1′-biphenyl, C14H10Br4 - Zhong Kai-Long; Zhou Yue; Zhang Tian-Yu; Yang Chao-Bo (Zeitschrift für Kristallographie - New Crystal Structures)
C14H10Br4, tetragonal, P43212 (no. 96), a = 6.8288(8) Å, c = 31.988(6) Å, V = 1491.7(5) Å3, Z = 4, R gt(F) = 0.0540, wR ref(F 2) = 0.1479, T = 193 K.